PRAKTIK AUTOCRATIC LEGALISM DI INDONESIA DALAM PROSES PERUBAHAN KEDUA ATAS UNDANG-UNDANG NO.30 TAHUN 2002 TENTANG KOMISI PEMBERANTASAN TINDAK PIDANA KORUPSI: Practice Of Autocratic Legalism In Indonesia In The Process Of The Second Amendment To Law No. 30 Of 2002 Concerning The Corruption Eradication Commision - Muhammad Fauzan Alaydrus; Ali Rido (AMICUS CURIAE, 2025)
Autocratic legalism is the practice of privatizing power that uses law as a pretext for action. The symptom of autocratic legalism is a contemporary issue that occurs in several Latin American countries. This symptom is also suspected to occur in Indonesia. In order to further examine the existence or absence of this symptom, the researcher examined it against the process of the second revision of Law Number 30 of 2002 concerning the Corruption Eradication Commission. For this reason, the author conducted a study based on the formulation of the following problems: 1. How is the practice of autocratic legalism in the second amendment to the Law on Corruption; 2. What is the impact of the practice of autocratic legalism on the institution of the KPK after the second amendment to Law No. 30 of 2002; This research is a normative legal research using secondary data as the main data analyzed qualitatively. The nature of the research is descriptive with deductive conclusions drawn. Based on the results of the study, the practice of autocratic legalism in the revision of the KPK Law includes: 1). The legislative process is fast and tends to be closed; 2). Collusion or conspiracy between the DPR and the President; 3). Manipulation of the law as a pretext for legitimacy; and 4). Co-optation of political parties. The impact is that the independence of the KPK is disrupted both institutionally and institutionally, thus significantly increasing the duties and functions of the KPK.